Firm-Level Expectations and Behavior in Response to the COVID-19 Crisis - Lukas Buchheim; Jonas Dovern; Carla Krolage; Sebastian Link (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies the determinants of firms' business outlook and managerial mitigation strategies in the wake of the COVID-19 crisis using a representative panel of German firms. We first demonstrate that the crisis amplifies pre-crisis weaknesses: Firms that appear relatively weak before the crisis are harder hit initially, and, on top of the initial impact, expect more difficulties for their businesses going forward. Consequently, such firms are first to cut employment and investment. Second, our results highlight that expectations regarding the duration of the shutdown—which, at this point of the crisis, exhibit plausibly random variation—are an important determinant of the chosen mitigation strategies: Firms that expect the shutdown to last longer are more likely to lay off workers and to cancel or postpone investment projects.
Keywords: D22; D84; E23; 330; expectations; firm behaviour; COVID-19; shutdown; employment; investment